BLOCKCHAIN TECHNOLOGY’S ROLE IN SECURING DATA AND PREVENTING CYBERATTACKS: A DETAILED REVIEW - Roopesh, Ms (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2024)
This systematic review examines the role of blockchain technology in enhancing data security and preventing cyberattacks across various sectors. Blockchain’s decentralized and immutable ledger system, secured through cryptographic mechanisms like cryptographic hashes and asymmetric encryption, offers robust protection against unauthorized access and data tampering. The study highlights blockchain’s ability to maintain data integrity and immutability, essential for applications requiring high levels of trust, such as financial transactions and healthcare records. The review also emphasizes the significance of smart contracts, which automate and enforce contract terms, thereby reducing human error and fraud. Sector-specific applications in finance, healthcare, supply chain management, and the Internet of Things demonstrate blockchain’s versatility in addressing diverse security challenges. However, significant challenges, including scalability issues, high energy consumption, and regulatory and legal hurdles, impede the widespread adoption of blockchain technology. Addressing these challenges is crucial for realizing blockchain’s full potential in cybersecurity. This review underscores the need for continued research and development to overcome these obstacles and fully harness blockchain’s capabilities in securing data and preventing cyberattacks.